Conservation of the dehiscence zone gene regulatory network in dicots and the role of the SEEDSTICK ortholog of California poppy (Eschscholzia californica) in fruit development - Dominik Lotz; Le Han Rössner; Katrin Ehlers; Doudou Kong; Clemens Rössner; Oliver Rupp; Annette Becker (EvoDevo)
Abstract Background Fruits, with their diverse shapes, colors, and flavors, represent a fascinating aspect of plant evolution and have played a significant role in human history and nutrition. Understanding the origins and evolutionary pathways of fruits offers valuable insights into plant diversity, ecological relationships, and the development of agricultural systems. Arabidopsis thaliana (Brassicaceae, core eudicot) and Eschscholzia californica (California poppy, Papaveraceae, sister group to core eudicots) both develop dry dehiscent fruits, with two valves separating explosively from the replum-like region upon maturation. This led to the hypothesis, that homologous gene regulatory networks direct fruit development and dehiscence in both species. Results Transcriptome analysis of separately collected valve and replum-like tissue of California poppy yielded the SEEDSTICK (STK) ortholog as candidate for dehiscence zone regulation. Expression analysis of STK orthologs from dry dehiscing fruits of legumes (Vicia faba, Glycine max and Pisum sativum) shows their involvement in fruit development. Functional analysis using Virus-Induced Gene Silencing (VIGS) showed premature rupture of fruits and clarified the roles of EscaSTK: an evolutionary conserved role in seed filling and seed coat development, and a novel role in restricting cell divisions in the inner cell layer of the valve. Conclusion Our analysis shows that the gene regulatory network described in Arabidopsis is significantly different in other dicots, even if their fruits form a dehiscence zone at the valve margins. The ortholog of STK, known to be involved in ovule development and seed abscission in Arabidopsis, was recruited to a network regulating fruit wall proliferation in California poppy. There, EscaSTK allows fruit maturation without premature capsule rupture, highlighting the importance of proper endocarp development for successful seed dispersal.